GEOTECHNICAL INVESTIGATION OF TIDAL FLOODING-RELATED ROAD SUBSIDENCE ON THE BONTANG-KUALA ROAD SECTION - Aco Wahyudi Efendi; Tukimun, Tukimun; Rizki Satria Putra; Amir Wardana (Bajang Institute, 2025)
The Bontang-Kuala road in East Kalimantan Province faces major problems due to daily tidal flooding and significant road subsidence. The objective of this study is to conduct a geotechnical analysis of the current conditions and develop more efficient solutions. Field surveys, soil investigations, and numerical analysis using the finite element method were employed in this study. To validate soil parameters, a back-analysis was conducted using ten years of subsidence data, which indicated a subsidence of 39.58 cm. The analysis results showed that conventional embankment reinforcement cannot withstand the required traffic load and may collapse. There are three treatment options: Pile slab structure, pile embankment with soil fill, and pile embankment with mortar foam fill. It was proven that each option meets the stability and technical design settlement requirements.